Serum ASGR2 level: an efficacy biomarker for balloon pulmonary angioplasty in patients with chronic thromboembolic pulmonary hypertension - Xu, Wei-Jie; Wang, Shang; Zhao, Qian-Hao; Xu, Jia-Yi; Hu, Xiao-Yi; Gong, Su-Gang; He, Jing; Qiu, Hong-Ling; Luo, Ci-Jun; Xu, Jian; Li, Hui-Ting; Li, Ze-Pu; et al. (Frontiers in Immunology, 2024)
Background This study aimed to employ plasma proteomics to investigate the molecular changes, pathway alterations, and potential novel biochemical markers associated with balloon pulmonary angioplasty (BPA) in patients with chronic thromboembolic pulmonary hypertension (CTEPH). Methods Pre- and post-BPA plasma samples from five CTEPH patients in the PRACTICE study were analyzed to identify differentially expressed proteins. Proteomic and bioinformatics analyses were conducted, and the identified proteins were further validated using ELISA assays in a separate cohort of the same study. Correlation and multivariate regression analyses were performed to investigate the associations between these differentially expressed proteins and clinical parameters. Results Significantly higher serum levels of asialoglycoprotein receptor 2 (ASGR2) were detected in 5 CTEPH patients compared to those in healthy individuals but decreased significantly after successful BPA procedures. The decrease in serum levels of ASGR2 after the completion of BPA procedures was further validated in a separate cohort of 48 patients with CTEPH [0.70 (0.51, 1.11) ng/mL vs. 0.38 (0.27, 0.59) ng/mL, P < 0.001]. Significant associations were found between the pre-BPA ASGR2 level and clinical parameters, including neutrophil percentage (R = 0.285, P < 0.05), platelet (PLT) count (R = 0.386, P < 0.05), and high-density lipoprotein cholesterol (HDL-C) before BPA (R = -0.285, P < 0.05). Significant associations were detected between post-BPA serum ASGR2 levels and lymphocyte percentage (LYM%) (R = 0.306, P < 0.05), neutrophil-to-lymphocyte ratio (R = -0.294, P < 0.05), and pulmonary vascular resistance after BPA (R = -0.35, P < 0.05). Multivariate stepwise regression analysis revealed that pre-BPA ASGR2 levels were associated with HDL-C and PLT count (both P < 0.001), while post-BPA ASGR2 levels were associated with LYM% (P < 0.05). Conclusion Serum levels of ASGR2 may be a biomarker for the effectiveness of BPA treatment in CTEPH patients. The pre-BPA serum level of ASGR2 in CTEPH patients was associated with HDL-C and the PLT count. The post-BPA serum level of ASGR2 was correlated with the LYM%, which may reflect aspects of immune and inflammatory status.